2011
DOI: 10.4236/ijoc.2011.14036
|View full text |Cite
|
Sign up to set email alerts
|

Vilsmeier Haack Adducts as Effective Reagents for Regioselective Nitration of Aromatic Compounds under Conventional and Non-Conventional Conditions

Abstract: Nitration of aromatic Compounds is triggered by Vilsmeier-Haack reagent (DMF/POCl3) or (DMF/SOCl2) in the presence of KNO3 or NaNO2 under conventional and non-conventional conditions. The reactions af- forded corresponding Nitro derivatives in very good yield with high regioselectivity. The results obtained in non-conventional methods (Micro wave irradiation, Grinding, Sonication) are comparable with those ob- tained under conventional conditions, but the reaction times of former conditions are substantially s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 26 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…In general, (DMF/POCl 3 ) or (DMF/SOCl 2 ) are used to generate an iminium salt intermediate salt can be used in the synthesis of a large number of heterocyclic compounds. Recently our group reported that bromo derivatives with KBr or NBS and nitro derivatives with KNO 3 or NaNO 2 using Vilsmeier-Haack reagent [7,8]. Encouraged by this result, we tried to use VH reagent (DMF/SOCl 2 and DMF/POCl 3 ) in presence of NaHSO 3 for sulfonation reactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, (DMF/POCl 3 ) or (DMF/SOCl 2 ) are used to generate an iminium salt intermediate salt can be used in the synthesis of a large number of heterocyclic compounds. Recently our group reported that bromo derivatives with KBr or NBS and nitro derivatives with KNO 3 or NaNO 2 using Vilsmeier-Haack reagent [7,8]. Encouraged by this result, we tried to use VH reagent (DMF/SOCl 2 and DMF/POCl 3 ) in presence of NaHSO 3 for sulfonation reactions.…”
Section: Resultsmentioning
confidence: 99%
“…Highly aggressive reactivity of SO 3 could be controlled by diluting and/or complexing the SO 3 to moderate reactivity level. Over the past decade, our group has also been actively involved in designing a variety of ecofriendly materials using micelleforming surfactants as catalysts and unconventional energy sources (such as microwave irradiation and ultrasound) to assist Vilsmeier-Haack (VH) reactions [7,8] and Hunsdiecker reactions [9,10]. Therefore, it has been proposed to develop an alternate path way for sulfonation of aromatic compounds using (DMF + Oxychloride)/NaHSO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…In several protocols, we have either completely avoided or minimized the use of mineral acids. [4][5][6][7][8][9][10] In 1902, Chattaway and Wadmore 11 reported the use of trichloroisocyanuric acid (TCCA) as a versatile oxidizing and chlorinating laboratory reagent, which is economically cheap, environmentally safe, less toxic, and easily available. 12 On the other hand, there has been an upsurge in the use of N,N′-dimethylformamide (DMF) by physical organic and organic chemists, because it is a polar aprotic solvent and exhibits hydrophilic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Ours is one among the several research groups, which has undertaken the development of certain protocols to achieve nitration by replacing an acid mixture. In several protocols, we have either completely avoided or minimized the use of mineral acids 4–10 . In 1902, Chattaway and Wadmore 11 reported the use of trichloroisocyanuric acid (TCCA) as a versatile oxidizing and chlorinating laboratory reagent, which is economically cheap, environmentally safe, less toxic, and easily available 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Since more than one decade our group is also actively working on exploiting the use of a variety of eco-friendly materials such as metal ions and surfactants as catalysts and non-conventional energy sources (such as microwave and ultra sound) to assist various organic transformations [24,25]. These reactions generally did not proceed at room temperature and is too sluggish even at elevated temperatures.…”
Section: Introductionmentioning
confidence: 99%